Effect of short-term macrophage depletion in the development of posterior capsule opacification in rodents. - Lois, N; Dawson, R; Townend, J; McKinnon, A; Smith, G; van't Hof, R; Van Rooijen, N; Forrester, J (2008)
AIM: To evaluate the role of macrophages in the development of posterior capsule opacification (PCO). METHODS: For this purpose, an extracapsular lens extraction was performed in 18 consecutive Sprague-Dawley rats. Animals were treated with liposomal clodronate (Cl(2)MDP-lip-treated group, n = 10) or phosphate-buffered saline (PBS) (control group, n = 8) 1 day preoperatively and on the first day postoperatively, and sacrificed 3 days postoperatively. Masked clinical, light microscopy and immunohistochemistry studies were conducted. The Fisher exact test and randomisation test were used to assess statistically differences between groups. RESULTS: A statistically significant reduction in the number of macrophages (ED1+, ED7+, ED8+) was found in the Cl(2)MDP-lip-treated group compared with the PBS-lip-treated group (p = 0.048, p = 0.004, p = 0.027, respectively). There were no statistically significant differences with regards to the presence/absence of central opacification (p = 0.29) and capsular wrinkling (p = 0.21) as detected clinically between groups. Similarly, a qualitative evaluation of the degree of PCO with regards to lens epithelial cell (LEC) proliferation, capsular wrinkling and Soemmerring ring formation showed no statistically significance between groups (p = 0.27, p = 0.061, p = 1.0, respectively). However, a statistically significant reduction in the number of lens epithelial cells (LEC) counted in the centre of the posterior capsule was found in the Cl(2)MDP-lip-treated group (p = 0.009). CONCLUSION: Depletion of macrophages was accompanied by a reduction in LEC in the centre of the posterior capsule in rodents.